Conveyor Pengangkut Sampah Otomatis dengan Load Cell dan Flow Sensor - Catur Harsito; Albert Xaverius; Singgih Dwi Prasetyo; Pipit Wulansari; Johan Alfian Pradana (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
Garbage has certainly been a classic problem which tends to get worse, especially in Jabodetabek area. Various attempts were made to solve the waste problem in the cities. This raises the writer's desire to make a tool that can clean trash in the river automatically, far-reaching, and effectively, namely the lifting garbage conveyor. With this design, garbage can be cleaned continuously because of the automatic system. Even if the volume of garbage in the river increases, the tool can increase the speed of cleaning the garbage by itself. With the sensor system, the tool can continue to operate, without allowing trash to accumulate, using energy effectively, and not requiring a lot of human labor. This tool is designed to cover the entire river and it is capable of being assembled. Because the tool can run automatically, it only takes 1 to 2 workers whose to supervise and do not need to work physically. This tool is easy to operate. To start this tool, you don't need special skills such as the ability to drive when using an excavator.